Changing qualifications : a review of qualifications policies and practices - Brugia, Mara [Mitarbeiter]; Le Mouillour, Isabelle [Mitarbeiter]; Pevec Grm, Slava [Mitarbeiter]; Psifidou, Rena [Mitarbeiter]; Zahilas, Loukas [Mitarbeiter]; Coles, Mike [Mitarbeiter]; Oates, Tim [Mitarbeiter]; Leney, Tom [Mitarbeiter]; Hanf, Georg [Mitarbeiter]; Raffe, David [Mitarbeiter]; Clematide, Bruno [Mitarbeiter]; Watters, Elizabeth [Mitarbeiter]; et al. (Publications Office of the European Union, 2010)
"Qualifications (or certificates and diplomas) are of crucial importance in modern societies. Individuals use qualifications not just to signal their personal, social and professional status; their access to education and training and the labour market is largely dependent on qualifications held. This study analyses the roles and funtions of qualifications in Europe today and shows how these are changing." Covering a wide range of sources, including an overview of Cedefop's own work and case studies of countries, it outlines four possible scenarios for developments in the next ten years, and identifies the cornerstones for a reform strategy. (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.2.3.2 Anforderungen & Bedarfe; G 2.3.4 Qualifikationswandel; G 1.2 Arbeitsmarkt; I 2.2 Europa; EU-Bildungspolitik; Qualifikation; Qualifikationsbegriff; Qualifikationswandel; Beziehung Bildungssystem Beschäftigungssystem; Beschäftigungsfähigkeit; Qualifikationsrahmen; Fallstudie; Bundesrepublik Deutschland; Dänemark; Frankreich; Irland; Vereinigtes Königreich; Europa